Building climate resilience of UK's rail network through a multihazard approach. Issue 8 (17th January 2019) - Green, Alex; Chmutina, Ksenia
Abstract : Climate projections suggest that the UK will be increasingly affected by climate-induced hazards in the future, exacerbating the potential for multihazard events to occur. This paper explores the extent to which climate resilience is being embedded in current and future rail transport infrastructure projects in London through use of a multihazard approach. It concludes that a multihazard approach is a relatively new concept and is therefore not currently being considered widely. However, opportunities for decision makers to explore its value to mitigate climate risks through collaborative working and further research exist – this paper recommends that two main stages are required to achieve this. Route 1 requires climate/hazard experts to identify and characterise the different hazard interactions that could occur, including their impact on the UK/London. Following this, route 2 involves the creation of multidisciplinary workshops to identify any multihazard vulnerabilities associated with different rail assets – potentially highlighting areas where further research is required. The paper concludes that although a London rail context has been adopted in order to understand the relevance of a multihazard approach, there is opportunity for it to be considered across many different sectors in the UK and the wider civil engineering industry.